2012
DOI: 10.3922/j.psns.2012.2.16
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal-cerebellar involvement in enhancement of performance in word-based BRT with the presence of background noise: An initial fMRI study.

Abstract: Background noise may impose deleterious effects on cognitive processing. However, noise below the threshold level may increase the ability to detect stimuli via stochastic resonance mechanisms (SR). The present study investigates whether task performance is deteriorated or enhanced by 5-dB SNR and, if the task performance is enhanced, whether this facilitation in performance points to a particular neural area that serves to attenuate noise and/or increase effective task performance. The areas of interest are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 60 publications
0
17
0
3
Order By: Relevance
“…The bilateral auditory areas including the right insula lobe seemed to be more sensitive to low frequency tone discrimination but only if the task is performed in noisy condition. Likewise, putamen and hippocampus, the two brain areas that have been known to be involved in motor performance and working memory respectively (Abdul Manan et al, 2012), showed significantly higher activation in quiet as compared to in noise because they are more sensitive to high frequency tones discrimination but only when the task is performed in quiet. In conjunction with the behavioral test results explained earlier, one possible explanation for the significant increase in the brain activation in the bilateral auditory areas for the respective (Noise > Quiet) condition mentioned above is to compensate for the degradation of cognitive processing performance that has been affected by the white noise which distract attention from the main tasks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The bilateral auditory areas including the right insula lobe seemed to be more sensitive to low frequency tone discrimination but only if the task is performed in noisy condition. Likewise, putamen and hippocampus, the two brain areas that have been known to be involved in motor performance and working memory respectively (Abdul Manan et al, 2012), showed significantly higher activation in quiet as compared to in noise because they are more sensitive to high frequency tones discrimination but only when the task is performed in quiet. In conjunction with the behavioral test results explained earlier, one possible explanation for the significant increase in the brain activation in the bilateral auditory areas for the respective (Noise > Quiet) condition mentioned above is to compensate for the degradation of cognitive processing performance that has been affected by the white noise which distract attention from the main tasks.…”
Section: Discussionmentioning
confidence: 99%
“…In conjunction with the behavioral test results explained earlier, one possible explanation for the significant increase in the brain activation in the bilateral auditory areas for the respective (Noise > Quiet) condition mentioned above is to compensate for the degradation of cognitive processing performance that has been affected by the white noise which distract attention from the main tasks. In our previous study on the effects of noise on verbal working memory processing, the bilateral primary auditory cortices have shown significant increase in activation in noisy condition as compared to in quiet (Abdul Manan et al, 2012). In the case of (Quiet > Noise) condition, comparison with behavioral test results is not possible due its one-way nature of test.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kawasan otak ini dipilih berdasarkan kepada keputusan pengkhususan kefungsian (Abdul Manan et al 2013;Manan et al 2015Manan et al , 2013Manan et al , 2012 (Yusoff et al 2011), pemprosesan penumpuan iaitu talamus (Alexander et al 2012) dan kawasan otak yang terlibat dalam pemprosesan ingatan bekerja iaitu girus presentral (PCG) (Mitchell et al 2000). Kawasan otak ini dipilih kerana peranan yang dimainkan semasa pemprosesan BRT.…”
Section: Analisis Data Fmriunclassified